2020
DOI: 10.1186/s12940-019-0558-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate factors driven typhus group rickettsiosis incidence dynamics in Xishuangbanna Dai autonomous prefecture of Yunnan province in China, 2005–2017

Abstract: Background: Typhus group rickettsiosis (TGR), which is a neglected vector-borne infectious disease, including epidemic typhus and endemic typhus. We explored the lag effects and nonlinear association between meteorological factors and TGR incidence in Xishuangbanna Dai autonomous prefecture from 2005 to 2017, China. Methods: A Poisson regression with a distributed lag nonlinear model (DLNM) was utilized to analyze TGR cases data and the contemporaneous meteorological data. Results: A J-shaped nonlinear associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Generally, temperature plays an important role in the number of reported insect-borne and rodent-borne diseases cases [42,[53][54][55][56]. However, typhus group rickettsiosis was negatively related to average temperature, average ground temperature, and extreme minimum temperature [13]. The same negative correlation was also found between temperature and schistosomiasis [47].…”
Section: The Relationship Between Meteorological Factors and Vector-b...mentioning
confidence: 83%
See 2 more Smart Citations
“…Generally, temperature plays an important role in the number of reported insect-borne and rodent-borne diseases cases [42,[53][54][55][56]. However, typhus group rickettsiosis was negatively related to average temperature, average ground temperature, and extreme minimum temperature [13]. The same negative correlation was also found between temperature and schistosomiasis [47].…”
Section: The Relationship Between Meteorological Factors and Vector-b...mentioning
confidence: 83%
“…The relationship between climate factors and vector-borne diseases was non-linear; a J-shape or reverse U-shape was always found between them, which means, respectively, that the risks increased continuously or increased and then decreased with the rise of certain meteorological factors. Temperature, precipitation, and humidity were the main parameters contributing to the transmission of vector-borne diseases [13,[50][51][52]. Generally, temperature plays an important role in the number of reported insect-borne and rodent-borne diseases cases [42,[53][54][55][56].…”
Section: The Relationship Between Meteorological Factors and Vector-b...mentioning
confidence: 99%
See 1 more Smart Citation
“…Xishuangbanna Dai autonomous prefecture (latitude 21°10′N-22°40′N, longitude 99°55′E-101°50′E) located in the southwestern part of China (Fig. 5), bordering Myanmar to the southwest and Laos to the southeast, with mild, warm and humid climate all year round with an annual average temperature from 18.6 to 22.9 °C, and an annual precipitation from 1347.4 to 1916.8 mm (Gao et al, 2020). Therefore, it is rich in animals and plants, belonging to Indo-Burma biodiversity hotspot (Liu et al, 2010;Myers, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the Xishuangbanna Dai autonomous prefecture is a mild, humid, and warm all year around. The annual average temperature is recorded from 18.6 to 22.9°C, while the annually precipitation was recorded from 1347.4 to 1916.8 mm (Gao et al, 2020). In order to understand the biodiversity of Heteropoda spiders in China and to study their dispersal route at China and global level, our colleagues of Hubei University conducted a series of surveys on huntsman spiders and yielded several Heteropoda species in Dai Autonomous Prefecture of Xishuangbanna during the last ten years.…”
Section: Introductionmentioning
confidence: 99%